Simulation modelling of public-private partnership in the Arctic regions - Olga Tarasova (European Regional Science Association (ERSA), 2016)
Arctic vector of economic development is now a strategic imperative for the Russian Federation. Apparently, severe climatic conditions, low population density, lack of infrastructure leave all Arctic projects outside the market and allow only nodular economic development of the Russian Arctic territories. The internal structure of these patches of economic activity should be justified with the help of economic-mathematical modeling. This becomes of particular importance given that all Arctic investment projects will for sure employ administrative and financial resources of the state along with private initiative. Views on state participation in the economy are different: from the invisible hand of Adam Smith's market to a tight state policy of Soviet administrative economy. On the other hand, it is impossible to use templates in the Russian Arctic: PPP best practices might not give results in risky northern conditions. Each group of projects should be simulated and all effects forecasted on the series of evaluative scenario calculations. Certain results in this direction have been obtained and described by the authors in previous works. The aim of the present work was to search for opportunities as well as to implement modifications of economic-mathematical models used for the assessment in order to improve the convenience of predictive scenario calculations and expand the analytical capabilities of instruments. The simulation model was modified in the following areas: 1. introduced an opportunity to observe the project's effects in dynamics. It is important when choosing a combination of measures of state support when taking into account the correlation of their effectiveness in various stages of implementation; 2. added a variability of projects' productivity; 3. added an option to specify the result year (up to which a forecast of the development ought to be done, and accordingly, all effects to be shown). The idea was that for different actors of the project different length of the forecast period could be important. Furthermore, long-term, medium-term and short-term period calculations may be required at once, and late on their correction would need on a regular basis; 4. added a possibility of variation of the construction period (two discrete provisions "handing on time" and "delay"). This is done for the convenience of reference in time of the projects in the case of a delay occurred on one of them and searching a mechanism to respond to such delays. With the help of the modified simulation model the authors generated a pack of scenarios, obtained their quantitative assessment and attempted to determine the optimal trajectory of Taimyr-Yakut ATPC's development. Key projects here are Tomtor and Popigai fields and the ports included in the logistic maintenance scheme - Tiksi, Khatanga, Yuryung-Khaya (provided transportation for export and Zheleznogorsk for processing). These projects are strategically important for Russia: having a wide range of applications in high-tech industries, those minerals could give rise to the Russian innovative development.
Keywords: C63; O18; R58; 330; Arctic investment projects; simulation modeling; scenario modeling